If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -6) = 20 Reorder the terms: 3(-6 + x) = 20 (-6 * 3 + x * 3) = 20 (-18 + 3x) = 20 Solving -18 + 3x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 3x = 20 + 18 Combine like terms: -18 + 18 = 0 0 + 3x = 20 + 18 3x = 20 + 18 Combine like terms: 20 + 18 = 38 3x = 38 Divide each side by '3'. x = 12.66666667 Simplifying x = 12.66666667
| 2x+3x+6=36 | | -3+2x+15=27 | | -52+2x=84+6x | | x^3+6x^2+6x+8=0 | | (3x+12)=5x | | 42=4x+4x-6 | | 4(3x+-5)+6=7(x-2)+6x | | 5x+7-2x+1=17 | | 3x-3+x-7+x=180 | | 4(3x+-5)+6=6x+2(3x-8) | | (4y+7)(9-y)=0 | | 3+4k-3k= | | x-(-2)=-7 | | -7y+5=8y+8 | | 4(3x+-5)+6=12x-14 | | 91-2x=9x-162 | | 5(9+-5.5)+3y=-4 | | 8x+11=6x+13 | | 2m+(-8m)= | | 5y-6x=-13 | | 4/5+1/8= | | (5n-20)=3n | | -x-6=-2x-1 | | D+5=3 | | 3k^2-10k+3=0 | | x+2=48 | | 256x+1=125x-2 | | 2/3x-1+1/6=9 | | 6x^3+14x^2-21x-49=0 | | x=3x+6x | | x=3x-6x | | x=3x-5-5x-26 |